2019
DOI: 10.2147/ott.s221657
|View full text |Cite
|
Sign up to set email alerts
|

<p>RGS4 Regulates Proliferation And Apoptosis Of NSCLC Cells Via microRNA-16 And Brain-Derived Neurotrophic Factor</p>

Abstract: PurposeRegulator of G-protein signaling (RGS) proteins are GTPase-activating proteins that target the α-subunit of heterotrimeric G proteins. Many studies have shown that RGS proteins contribute to tumorigenesis and metastasis. However, the mechanism in which RGS proteins, especially RGS4, affect the development of non-small cell lung cancer (NSCLC) remains unclear. The aim of this study was to characterize the role of RGS4 in NSCLC.MethodsRGS4 expression in NSCLC tissues was assessed using an immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Antagonizing its overexpression in GBM may be an attractive strategy for oncotherapy. A recent body of literature suggests the involvement of RGS4 in breast [39] and non-small cell lung (NSCL) cancers [40]; however, the physiological function of RGS4 in GBM and specifically in GSCs is not known, with little published data to date [41]. Our studies demonstrate that RGS4 is highly expressed in clinical specimens of glioblastoma substantiated by the TCGA data.…”
Section: Discussionsupporting
confidence: 75%
“…Antagonizing its overexpression in GBM may be an attractive strategy for oncotherapy. A recent body of literature suggests the involvement of RGS4 in breast [39] and non-small cell lung (NSCL) cancers [40]; however, the physiological function of RGS4 in GBM and specifically in GSCs is not known, with little published data to date [41]. Our studies demonstrate that RGS4 is highly expressed in clinical specimens of glioblastoma substantiated by the TCGA data.…”
Section: Discussionsupporting
confidence: 75%
“…RGS4, located on chromosome 1q23‐3, is a regulator of G‐protein and can promote various downstream signals related to cell survival, apoptosis and migration. Abnormal expression of RGS4 is related to the occurrence and development of various malignancies such as pediatric nephroblastoma 24 and non‐small cell lung cancer 25 . Xie et al 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, He et al . have found increased RGS4 protein levels in non-small cell lung cancer cells [ 46 ]. They showed that RGS4 knockdown inhibits cell proliferation and induces apoptosis, and that RGS4 negatively regulates the tumor suppressor, microRNA-16.…”
Section: Discussionmentioning
confidence: 99%